Remote Magnetic Navigation: A Focus on Catheter Ablation of Ventricular Arrhythmias. (March 2016) - AAGAARD, PHILIP; NATALE, ANDREA; BRICENO, DAVID; NAKAGAWA, HIROSHI; MOHANTY, SANGHAMITRA; GIANNI, CAROLA; BURKHARDT, J. DAVID; DI BIASE, LUIGI
A Focus on Catheter Ablation of Ventricular Arrhythmias: VT ablation is based on percutaneous catheter insertion under fluoroscopic guidance to selectively destroy (i.e., ablate) myocardial tissue regions responsible for the initiation or propagation of ventricular arrhythmias. Although the last decade has witnessed a rapid evolution of ablation equipment and techniques, the control over catheter movement during manual ablation has remained largely unchanged. Moreover, the procedures are long, and require ergonomically unfavorable positions, which can lead to operator fatigue. In an attempt to overcome these constraints, several technical advancements, including remote magnetic navigation (RMN), have been developed. RMN utilizes a magnetic field to remotely manipulate specially designed soft‐tip ablation catheters anywhere in the x, y, or z plane inside the patient's chest. RMN also facilitates titration of the contact force between the catheter and the myocardial tissue, which may reduce the risk of complications while ensuring adequate lesion formation. There are several non‐randomized studies showing that RMN has similar efficacy to manual ablation, while complication rates and total radiation exposure appears to be lower. Although these data are promising, larger randomized studies are needed to prove that RMN is superior to manual ablation of VT.